KELAYAKAN FINANSIAL USAHA PENGOLAHAN IKAN ASIN DI KECAMATAN SERUYAN HILIR KABUPATEN SERUYAN KALIMANTAN TENGAH - Lili Winarti (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
This study aimed to analyze the financial feasibility of salted fish processing business  Seruyan Hilir in district Seruyan. The method used is the method of census, census method is a research method that uses all individuals in the population so that in this study did not use samples. Analysis of the data used is qualitative analysis to analyze the costs incurred for activities ranging from the cost of investment, production operations and financial analysis used to determine feasible or not its processing business, salted fish using the criteria for eligibility of investment are: Net Present Value ( NPV), Internal rate of Return (IRR), Net Benefit Cost ratio (Net B / C), Payback Period and sensitivity analysis switching value to determine the sensitivity level of effort toward the changes to assumptions used for example only the first assumption the price of raw materials fresh fish rose 10%, assuming both the selling price of salted fish down 10%, and assuming a third the price of raw materials fresh fish rose 10% and the price of salted fish down 10% on the analysis finasial processing business, salted fish seen on the criteria of investment used salted fish processing business is still feasible to be developed or executed and based on the analysis of switching value that the reduction in the selling price of salted fish is more sensitive than the increase in raw material use fresh fish.